2018
DOI: 10.3390/ma11020290
|View full text |Cite
|
Sign up to set email alerts
|

Printing Smart Designs of Light Emitting Devices with Maintained Textile Properties

Abstract: To maintain typical textile properties, smart designs of light emitting devices are printed directly onto textile substrates. A first approach shows improved designs for alternating current powder electroluminescence (ACPEL) devices. A configuration with the following build-up, starting from the textile substrate, was applied using the screen printing technique: silver (10 µm)/barium titanate (10 µm)/zinc-oxide (10 µm) and poly(3,4-ethylenedioxythiophene)poly(styrenesulfonate) (10 µm). Textile properties such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Miura et al developed a foldable PEDOT:PSS/PVA fiber by wet spinning that exhibits a repeatable contraction motion at air by applying alternating square-wave voltages between 0 and 8 V [107]. Verboven et al reported an OLED with maintained textile properties by screen printing of silver as a bottom electrode, barium titanate as a dielectric, copper-dopped zinc-oxide as an active layer and PEDOT:PSS as a top electrode on polyester fabric that requires 3-5 V power supply [108]. The thickness of the OLED on the textile fabric was only 0.5 µm which is a good platform for wearable application; the schematic illustration and actual OLED are shown in Figure 9.…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miura et al developed a foldable PEDOT:PSS/PVA fiber by wet spinning that exhibits a repeatable contraction motion at air by applying alternating square-wave voltages between 0 and 8 V [107]. Verboven et al reported an OLED with maintained textile properties by screen printing of silver as a bottom electrode, barium titanate as a dielectric, copper-dopped zinc-oxide as an active layer and PEDOT:PSS as a top electrode on polyester fabric that requires 3-5 V power supply [108]. The thickness of the OLED on the textile fabric was only 0.5 µm which is a good platform for wearable application; the schematic illustration and actual OLED are shown in Figure 9.…”
Section: Other Applicationsmentioning
confidence: 99%
“…(a) Build-up of the alternating current powder electroluminescence technology; (b) OLED stack printed on a textile. Adapted from[108].…”
mentioning
confidence: 99%
“…-The process of lining the fabric using an electrically conductive polymer (22) A B Figure (8) illustrates the effect after printing the ACPEL. (17) ed among the non-textile applications. During the recent years, smart textile section has opened new ways to functionalize thermochromism.…”
Section: 51conductive Coatingmentioning
confidence: 99%
“…18 Suitable substrates for EL devices include but are not limited to paper, 19 PET (polyethylene terephthalate) films, glass, and textiles. 20,21 Generally, two production methods must be distinguished: first, the forward architecture method with a transparent front electrode coated or printed directly onto the substrate and second the reverse architecture method, where the transparent layer is the final layer applied. 22 The forward architecture is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%